2006
DOI: 10.1007/s10457-006-9008-7
|View full text |Cite
|
Sign up to set email alerts
|

Farming carbon: an economic analysis of agroforestry for carbon sequestration and dryland salinity reduction in Western Australia

Abstract: The widespread removal of native trees from the agricultural zone and replacement with annual crops and pastures is a major cause of dryland salinity in Australia. It has been recognised that a large proportion of the landscape needs to be replanted to trees to prevent further salinisation. However, for much of the agricultural zone, agroforestry is not an option due to lack of species that can viably generate the products currently demanded by the market. The emerging carbon market may provide a new agrofores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 12 publications
(9 reference statements)
2
26
0
Order By: Relevance
“…Thus, payments to land managers for sequestering C in agricultural soils and forestry projects, not only as sink projects under the Clean Development Mechanism (CDM) of the Kyoto Treaty (Zomer et al 2008) but also for enhancing ecosystem services would be an important strategy to alleviate poverty and advance regional/global food security. Selling credits of soil carbon sequestered through restoration of salt-affected (Flugge and Abadi 2006;Lal 2010) and other degraded/desertified soils (Lal 2009) would promote the concept of "farming carbon", a step towards achieving the U.N. Millennium Development Goals of combating poverty and reducing hunger. The term "Farming Carbon" implies increasing the carbon pool (stock) in soils (and trees) with the purpose of trading carbon thus sequestered as a farm commodity similar to that of trading corn, soybeans, milk, meat, etc.…”
Section: Cost Effectiveness and Payments For Ecosystem Servicesmentioning
confidence: 99%
“…Thus, payments to land managers for sequestering C in agricultural soils and forestry projects, not only as sink projects under the Clean Development Mechanism (CDM) of the Kyoto Treaty (Zomer et al 2008) but also for enhancing ecosystem services would be an important strategy to alleviate poverty and advance regional/global food security. Selling credits of soil carbon sequestered through restoration of salt-affected (Flugge and Abadi 2006;Lal 2010) and other degraded/desertified soils (Lal 2009) would promote the concept of "farming carbon", a step towards achieving the U.N. Millennium Development Goals of combating poverty and reducing hunger. The term "Farming Carbon" implies increasing the carbon pool (stock) in soils (and trees) with the purpose of trading carbon thus sequestered as a farm commodity similar to that of trading corn, soybeans, milk, meat, etc.…”
Section: Cost Effectiveness and Payments For Ecosystem Servicesmentioning
confidence: 99%
“…The unstable nature of the carbon market is an important consideration on the expansion of AFS for climate change mitigation. To date price of carbon at global market has decreased considerably in the last years from USD 16 to nearly USD 7 . A modeling of strict carbon farming in the Western Australia found that cost of carbon farming was at USD 45/tCO 2 ‐eq and USD 66/tCO 2 ‐eq for wheatbelts .…”
Section: Adaptationmentioning
confidence: 99%
“…Nevertheless, some research effort has been devoted to estimating average abatement costs in broadacre agriculture (Appendix S2). Flugge and Abadi (), Kragt et al . () and Thamo et al .…”
Section: Introductionmentioning
confidence: 99%